Visual Politics in American Dance Film: Representation and Disparity - Hagan, Cara (The International Journal of Screendance, 2017)
<span style="color: #000000; font-family: Helvetica, arial, sans-serif; font-size: 14px; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: 22px; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; display: inline !important; float: none;">This article explores stylistic and demographic commonalities in American dance film through the curatorial lens of <em style="-webkit-print-color-adjust: exact; color: #000000; font-family: Helvetica, arial, sans-serif; font-size: 14px; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: 22px; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px;">American Dance Festival’s Movies by Movers<span style="color: #000000; font-family: Helvetica, arial, sans-serif; font-size: 14px; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: 22px; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; display: inline !important; float: none;">, an international dance film festival. While calling into question how the dance film community can be more aware of the culture created on screen by makers and presenters, I reveal instances of representational disparity found in American dance film while examining the relationship of dance film to ideologies perpetuated by mass media and the world of professional dance.